Comunicare gli spazi della salute: il set “Isola dei pittogrammi” per il wayfinding ospedaliero - Fiammetta Pilozzi (Culture e Studi del Sociale, 2018)
The study explores how hospital wayfinding can employ communication design to improve the outpatient experience by using a pictograms based signals system. Communication de- sign might support and empower wayfinding processes in hospitals, where high levels of stress, anxiety and uncertainty can compromise the ability to understand and navigate the environment. The study produced a new set of pictograms for health communication named “Island of pictograms” implemented in the Fatebenefratelli - Isola Tiberina Hospital in Rome. The new set is based on the “HablamosJuntos” set and it represents the first open source set of pictograms for health communication whose comprehensibility has been tested in the Italian cultural (and multicultural) context.